Learning Based Voice Transmission through Wifi Network - Devi, S (International Journal of Computer Sciences and Engineering, 2025)
The use of Wi-Fi is increasing day-by-day. The use of Wi-Fi enabled phones as android phones, and their communication within a wireless LAN is to be discussed in this paper. This proposed system is in the form of GAN telecommunication network that allows data and voice transmissions within a specific range of interconnected networks. Each mobile device connects to a device which hosts Server which is a part of the network and identifies itself in the routing table. In proposal model allows free calls within the network with a high quality of voice transmission